3(x+6)=3(x+10)

Simple and best practice solution for 3(x+6)=3(x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+6)=3(x+10) equation:


Simplifying
3(x + 6) = 3(x + 10)

Reorder the terms:
3(6 + x) = 3(x + 10)
(6 * 3 + x * 3) = 3(x + 10)
(18 + 3x) = 3(x + 10)

Reorder the terms:
18 + 3x = 3(10 + x)
18 + 3x = (10 * 3 + x * 3)
18 + 3x = (30 + 3x)

Add '-3x' to each side of the equation.
18 + 3x + -3x = 30 + 3x + -3x

Combine like terms: 3x + -3x = 0
18 + 0 = 30 + 3x + -3x
18 = 30 + 3x + -3x

Combine like terms: 3x + -3x = 0
18 = 30 + 0
18 = 30

Solving
18 = 30

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10+4p=86 | | 64x+70=180 | | 5-3x=-26 | | 2(6-5x)=5x+9 | | 48-n^2=2n | | [-9]-[-8]= | | 6y+36=9y | | 5(x+7)=5(x+11) | | 3x-9=75-9x | | 2(x+6)=5x+9 | | (21+10)-9j=-277 | | 0=x^2+38x | | 8-10x=6x+1 | | 9x+3-10=3(3+x) | | 1=a(0+b)(0-7.1) | | ln(x)=3.78 | | 23=3p+1 | | 8x=11y | | 4n+38=-3(n-1) | | 2x+14=-4x-19 | | -3(3z+3)*3z=-53 | | -2+5w-7+9=-7 | | -3(2t-2)+4t=7t-7 | | -3(3z+3)+3z= | | 4y+7-y=10y+3y | | n+(n+1)+(n+2)=171 | | 30+0.25*n=59.50 | | y=3x+49 | | (5x+3)(4x-3)=0 | | 2n+5y+5n-6y-2n= | | 3f-12=3[f-12] | | 3c=6+2c |

Equations solver categories